Constitutive expression of VviNAC17 transcription factor significantly induces the synthesis of flavonoids and other phenolics in transgenic grape berry cells - Badim, Hélder (2022)
VviNAC17 is a grapevine transcription factor activated by ABA. Because ABA has been proposed as the main signal modulating the secondary metabolism in grape berry skins, here we postulated VviNAC17 as a positive regulator of secondary metabolism in grape cells. To validate the hypothesis, VviNAC17 was constitutively and stably overexpressed in grape berry suspension-cultured cells of Gamay Fréaux cv. by Agrobacterium-mediated transformation. Targeted transcriptional analyses by qPCR showed that several genes involved the phenylpropanoid (VviPAL1), stilbenoid (VviSTS1) and flavonoid pathways (VviDFR, VviLAR1, VviANR, VviLDOX, and VviUFGT1), as well as anthocyanin vacuolar transport and accumulation (VviGST4 and VvMATE1) were significantly upregulated in VviNAC17-overexpressing transgenic cells, which translated in the stimulation of a number of enzymatic activities in those pathways. This was the case of phenylalanine ammonia lyase (PAL) and UDP-glucose:flavonoid 3-O-glucosyltransferase (UFGT) that were about 2-fold and 3.5-fold higher in VviNAC17-overexpressing cells than in control cells. VviNAC17-overexpressing cells accumulated significantly higher amounts of anthocyanins, proanthocyanidins, total flavonoids and total phenolics. These findings confirmed that VviNAC17 is an important positive regulator of secondary metabolism in grapevine contributing to the accumulation of important berry quality-related secondary metabolites.